Certain Subclass of $p$-Valent Meromorphic Analytic Functions Involving Certain Integral Operator (Analysis in Theory and Applications, 2012)
The purpose of the present paper is to introduce a new subclass of $p$−valent meromorphic functions by using certain integral operator and to investigate various properties for this subclass.